Using information technology : a practical introduction to computers and communications - Williams, Brian K.; Sawyer, Stacey C.; Hutchinson, Sarah E. (Boston : Irwin, 1999)
Computer Science
Includes index
1999-06-28
Keywords: Computers; Information technologies; Tele communications